Classes of exact wave functions for general time-dependent Dirac Hamiltonians in [Formula Presented] dimensions - de Castro, A. S. [UNESP]; de Souza Dutra, A. [UNESP] (American Physical Society (APS), 2003)
In this work we construct two classes of exact solutions for the most general time-dependent Dirac Hamiltonian in [Formula Presented] dimensions. Some problems regarding some formal solutions in the literature are discussed. Finally the possibility of existence of a generalized Lewis-Riesenfeld invariant connected with such solutions is discussed. © 2003 The American Physical Society.